1998
DOI: 10.1037/0021-9010.83.5.788
|View full text |Cite
|
Sign up to set email alerts
|

The value of voice in participative decision making.

Abstract: Relying on concepts found in prospect theory (D. Kahneman & A. Tversky, 1979), the value function of voice-based participation (i.e., the relationship between the amount of voice received and the value attached to that quantity) was examined. In keeping with tenets of prospect theory, the value function of voice exhibited a nonlinear pattern. Points were identified in which voice displayed significant improvements and diminishing marginal returns on response measures of process fairness, decision control, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 23 publications
6
47
0
Order By: Relevance
“…The current study seeks to replicate and extend previous research examining the value function for voice (Hunton et al, 1998). Consistent with this goal, we expect to replicate results of earlier studies that document a nonlinear value function for voice.…”
Section: Voice Research and Prospect Theorysupporting
confidence: 78%
See 4 more Smart Citations
“…The current study seeks to replicate and extend previous research examining the value function for voice (Hunton et al, 1998). Consistent with this goal, we expect to replicate results of earlier studies that document a nonlinear value function for voice.…”
Section: Voice Research and Prospect Theorysupporting
confidence: 78%
“…Research cited earlier, by Hunton et al (1998), directly supports theorizing by Kahneman and Tversky (1979). Hunton et al (1998) reported that increases in the magnitude of voice were associated with declining increases in the value of voice.…”
Section: Voice Research and Prospect Theorysupporting
confidence: 62%
See 3 more Smart Citations